The Influence of Training, Rewards and Punishment on Employee Performance at The Grand Serela Hotel Yogyakarta - Simamora, Lambas Gratian; Mardiana, Tri (Universitas Mercu Buana, 2024)
This study aims to determine the effect of Training, Reward, and Punishment on Employee Performance of Grand Serela Yogyakarta hotel. The data collection technique used is the census technique or saturated sampling using a questionnaire. The data analysis method in this study used multiple regression analysis techniques using SPSS 25. This research is a casual associative research using a quantitative approach. The population in this study were all employees at Grand Serela Hotel Yogyakarta. The number of samples used in this study were 38 respondents. The results of this study reveal that training, reward and punishment have a joint effect on employee performance at the Grand Serela Yogyakarta Hotel, and training and the most dominant variable and influence on employee performance is the training variable..